Project Portfolio – Competitive Advantage for Design&Construction Companies Marketing Their Activities - Ionela Claudia ALECSA (ȘTIRBEȚ); Florin POPESCU (Revista de Management Comparat International)
Complex markets, intense competition, advanced technologies, demanding customers and prudent shareholders require marketing intelligent. To understand the markets evolving and how can be modeled in order to identify better opportunities before others, to beat competitors in a much more intelligent than reducing tariffs, to innovate radically in new directions, to establish lasting relationships with customers and provide substantial gains to shareholders, it requires an approach based on exploitting competitive advantange. This is the very dynamic construction market, within its design and construction services. This paper presents an analysis on marketing methods to attract clients with the main aim of this research to identify the importance of Project Portfolio as a competitive advantage in the construction market whereas companies are constantly challenged to adopt survival and growth strategies, generating "projects" that make them internationally competitive and support winning contracts. Additional, tools used in marketing design and construction projects and services were studied in order to rank the importance/ position of the Project Portfolio related to volume/ values of signed contracts. In this higher competitive environment, where companies do their best to adapt changes, how should they market better and effective? The analysis was performed on top 100 Romanian design&engineering companies and top 100 construction companies, although the questionnaire survey was sent to top 150 companies in the market, but 100 responses were received. Based on the questionnaire’s findings, project portfolio, recommendations and ability to further diversify the company's portfolio services were ranked top three identified to attract investors and clients.